Economic Value Added (EVA) And Market Value Added (MVA) As Financial Performance Measurement Tools (Study Of Telecommunication Companies On The IDX 2018-2022) - Okta Alvioni; Sri Adji Prabawa (Jurnal Mantik, 2024)
Economic Value Added (EVA) and Market Value Added (MVA) are important for measuring financial performance based on value. The purpose of this study is to analyze and measure the financial performance of Telecommunication Companies listed on the IDX using the Economic Value Added and Market Value Added methods in 2018- 2022. The results showed that based on the analysis of the company's financial performance with the EVA method, the companies TLKM, ISAT, EXCL, TBIG, TOWR, BALI, LINK and IBST have an average positive value, which means that the company has succeeded in creating economic added value for the company. While the average FREN company shows a negative EVA value which explains that the company cannot provide economic added value to the company. In the analysis of the company's financial performance with MVA, the companies TLKM, ISAT, EXCL, TBIG, TOWR, BALI, LINK, and IBST for the period 2018 – 2022 produce positive values, so the management shows good performance and has been able to create and add wealth for shareholders and the company. Meanwhile, the FREN company during the 2018-2022 period shows a negative value where management is unable to create or increase wealth for shareholders